2022
DOI: 10.1021/acs.accounts.1c00609
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical CO2 Reduction Catalyzed by Binuclear LRe2(CO)6Cl2 and LMn2(CO)6Br2 Complexes with an Internal Proton Source

Abstract: This paper represents the f irst binuclear Mn(CO) 3 that catalyzes the CO 2 electroreduction forming CO and formic acid. We investigate the impact of the two metal centers and the proton relay on product formation, reaction rate, and overpotential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…6 Many mechanistic details have been revealed; for example, the rhenium (Re) catalyst can proceed via a pathway producing CO and CO 3 2− or by a faster pathway occurring at a larger overpotential that generates CO and H 2 O. 7 On the other hand, the manganese (Mn) precatalyst exhibits similar trends but deviates from Re with regard to its propensity to rapidly form the dimeric metal−metal-bonded species upon one-electron reduction. 8−10 Bulky mesityl substituents near the Mn center slow the rate of dimerization and instead promote the low-overpotential pathway, which ultimately furnishes a more active catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Many mechanistic details have been revealed; for example, the rhenium (Re) catalyst can proceed via a pathway producing CO and CO 3 2− or by a faster pathway occurring at a larger overpotential that generates CO and H 2 O. 7 On the other hand, the manganese (Mn) precatalyst exhibits similar trends but deviates from Re with regard to its propensity to rapidly form the dimeric metal−metal-bonded species upon one-electron reduction. 8−10 Bulky mesityl substituents near the Mn center slow the rate of dimerization and instead promote the low-overpotential pathway, which ultimately furnishes a more active catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nearly 3 decades later, Deronzier and co-workers showed that the first-row metal congener [Mn­(bpy)­(CO) 3 Br] was also active for electrochemical CO 2 reduction in the presence of an added proton source . Many mechanistic details have been revealed; for example, the rhenium (Re) catalyst can proceed via a pathway producing CO and CO 3 2– or by a faster pathway occurring at a larger overpotential that generates CO and H 2 O . On the other hand, the manganese (Mn) precatalyst exhibits similar trends but deviates from Re with regard to its propensity to rapidly form the dimeric metal–metal-bonded species upon one-electron reduction. Bulky mesityl substituents near the Mn center slow the rate of dimerization and instead promote the low-overpotential pathway, which ultimately furnishes a more active catalyst. , The dimer itself is an electroactive species as well, whereby the Mn–Mn bond is cleaved by insertion of CO 2 , catalyzing the liberation of CO. , Other works have contributed to the development of a variety of Group 7 metal complexes based on these initial systems and have demonstrated an array of functions within the primary and secondary coordination spheres. , …”
Section: Introductionmentioning
confidence: 99%
“…Metal complexes with ligands containing the NH functionality have gained importance in catalysis since the NH arm can serve as an anchor for substrate recognition, thus enhancing catalyst selective and activity . A proton source located at the proximity of the metal center has been widely investigated in the proton-coupled electron transfer reduction of small molecules relevant in energy conversion reactions such as hydrogen evolution , and CO 2 reduction. It was proposed to modulate the redox properties, aid in the stabilization of intermediates, or impact the kinetics due to the increased local proton concentration. Furthermore, deprotonation of the NH group is known to modify the electronic and geometric structure of such complexes. …”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of [Re(bpy)(CO) 3 Cl] by Lehn et al in 1983, 2 numerous studies have elucidated mechanistic detail relating its structure–function as a homogeneous electrocatalyst for CO 2 -to-CO conversion in organic solvents. 3–6 For example, the Re catalyst can mediate this process via a disproportionation pathway that produces CO and CO 3 2− , or utilize a faster pathway occurring at a larger overpotential that generates CO and H 2 O in the presence of a proton source. 3–5 Many researchers have contributed towards development of various group 7 metal complexes based on this initial system and have demonstrated an array of functionality within the primary and secondary coordination sphere with the aim of improving catalyst performance, 3–5,7,8 and/or controlling the reaction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…3–6 For example, the Re catalyst can mediate this process via a disproportionation pathway that produces CO and CO 3 2− , or utilize a faster pathway occurring at a larger overpotential that generates CO and H 2 O in the presence of a proton source. 3–5 Many researchers have contributed towards development of various group 7 metal complexes based on this initial system and have demonstrated an array of functionality within the primary and secondary coordination sphere with the aim of improving catalyst performance, 3–5,7,8 and/or controlling the reaction pathway. 9 Notably, a pair of bimetallic [Re(bpy)(CO) 3 Cl] systems reported by Jurss and co-workers showed that spatial orientation and appropriate spacing between the two catalyst centres can significantly improve catalyst activity by avoiding Re–Re dimerization (a prevalent deactivation pathway).…”
Section: Introductionmentioning
confidence: 99%